Jawabanmu

2014-05-21T15:26:19+07:00
g(x) = ( 3x² + 6 ) ( 2x - 7 )
g'(x) = 6x(2x-7) + (3x²+6)(2)
       = 12x² - 42x + 6x² + 12
       = 18x² - 42x + 12
atau
g(x) = 6x³ - 21x² + 12x -42
g'(x) = 18x² - 42x + 12

APA KABAR TAZLHA
Jawaban paling cerdas!
2014-05-21T15:29:01+07:00
G(x) = ( 3x² + 6 ) ( 2x - 7 )

misalkan u = 3x² + 6 maka u' = 6x
              v = 2x - 7 maka v' = 2

f '(x) = u'.v + uv'
       = 6x . (2x - 7) + (3x² + 6) . 2
       = 12x
² - 42x + 6x² + 12
       = 18x
² - 42x + 12
1 5 1